Temples and towns in Roman Iberia : the social and architectural dynamics of sanctuary designs from the third century B.C. to the third century A.D. - Mierse, William E. (University of California Press, 1999)
"Temples and Towns is the first comparative study of Roman sanctuary design for the six centuries of architecture on the Iberian Peninsula, from the arrival of the Romans in the third century B.C. until the decline of urban life on the peninsula in the third century A.D. During these six centuries, the peninsula became an important influence in the Roman world. The area supplied writers, politicians, and emperors, a fact acknowledged by Romanists for centuries. But study of the peninsula itself has often been brushed aside as insignificant and uninteresting. In Temples and Towns in Roman Iberia Mierse challenges such a view."--Jacket